Divide
4y^ - 8y^4 / 2y^3
Divide
4y^ - 8y^4 / 2y^3
to make this easier, lets rewrite the equation:
4/2(y^(-8y^4))/(y^3) = 2(y^(-8y^4))/(y^3)
when you divide by powers with the same base, (in this example, base "y") you subtract.
so,
2(y^(-8y^4))/(y^3) = 2(y^((-8y^4)-3))
Hope this helps! :)
a^{m} • a^{n} = a^{m + n}
a^{m} ÷ a^{n} = a^{m - n }
1
a^{ - m }= ——
a^{m}
~~~~~~~~~~~
4 y^{ -8} y^{4} 4
————— = —— y^{ - 8 + 4 - 3 }
2 y^{3} 2
2
= 2y^{ - 7} = ——
y^{7}
Comments
I apologize. It seems I misinterpreted your question =X The above answer is for y^(-8y^4)/y^3
Thanks
Comment